CRX Expression in Pluripotent Stem Cell‐Derived Photoreceptors Marks a Transplantable Subpopulation of Early Cones. (30th January 2019) - Collin, Joseph; Zerti, Darin; Queen, Rachel; Santos‐Ferreira, Tiago; Bauer, Roman; Coxhead, Jonathan; Hussain, Rafiqul; Steel, David; Mellough, Carla; Ader, Marius; Sernagor, Evelyne; Armstrong, Lyle; et al.
Abstract: Death of photoreceptors is a common cause of age‐related and inherited retinal dystrophies, and thus their replenishment from renewable stem cell sources is a highly desirable therapeutic goal. Human pluripotent stem cells provide a useful cell source in view of their limitless self‐renewal capacity and potential to not only differentiate into cells of the retina but also self‐organize into tissue with structure akin to the human retina as part of three‐dimensional retinal organoids. Photoreceptor precursors have been isolated from differentiating human pluripotent stem cells through application of cell surface markers or fluorescent reporter approaches and shown to have a similar transcriptome to fetal photoreceptors. In this study, we investigated the transcriptional profile of CRX‐expressing photoreceptor precursors derived from human pluripotent stem cells and their engraftment capacity in an animal model of retinitis pigmentosa ( Pde6brd1 ), which is characterized by rapid photoreceptor degeneration. Single cell RNA‐Seq analysis revealed the presence of a dominant cell cluster comprising 72% of the cells, which displayed the hallmarks of early cone photoreceptor expression. When transplanted subretinally into the Pde6brd1 mice, the CRX + cells settled next to the inner nuclear layer and made connections with the inner neurons of the host retina, and approximately one‐third of them expressed the pan cone marker, Arrestin 3, indicating further maturation upon integration into the host retina. Together, our data provide valuable molecular insights into the transcriptional profile of human pluripotent stem cells‐derived CRX + photoreceptor precursors and indicate their usefulness as a source of transplantable cone photoreceptors. Stem Cells 2019;37:609–622 Abstract : Single cell RNA‐Seq analysis of a transplantable hESC‐derived early cone subpopulation.